Pro Kontra Cryptocurrency:: Studi Komparatif Fikih Muamalah - Faisol Habibi; Oman Fathurohman SW (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2024)
This study aims to analyze Islamic scholars' views on the halal or haram status of cryptocurrency in financial transactions according to Islamic jurisprudence (fiqh muamalah). Using a qualitative approach and comparative analysis method, this research explores the opinions of scholars and Islamic financial institutions regarding the use of cryptocurrency as a transactional tool. The results indicate two main groups of views: one group supports the use of cryptocurrency with specific conditions that align with Sharia, while the other group rejects it due to the presence of gharar (uncertainty) and maisir (speculation) in its use. This study provides a deeper understanding of the similarities and differences in scholars' arguments and their implications for Shariah decisions in the context of Islamic economics. The conclusion of this study is the importance of regulation and clear guidelines to ensure cryptocurrency’s compliance with Sharia principles.